Internal and External Factors Affecting Risk Management in Credit Services to Members of Agricultural Cooperatives and Farmers in Loei Province, Thailand - Kaew-arsa, Ratchanee; Kokanuch, Anchalee (KKBS Journal of Business Administration and Accountancy, 2024)
The objective of this research was to examine internal and external factors affecting risk management in providing credit services to members of agricultural cooperatives and farmer groups in Loei province, Thailand. The study population consisted of 90 individuals. They are individuals with authority to approve credit for agricultural cooperatives and farmer groups, including the chairman of the agricultural cooperative committee in Loei province, totaling 37 individuals, and the chairman of the farmer group committee in Loei province, totaling 53 individuals. Research tools included questionnaires, statistical analyses such as percentage, mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The research findings indicated that opinions regarding internal factor related to credit service management ranked highest, followed by opinions on risk management in credit service management and external factor, respectively. Additionally, the research results showed that both internal and external factors influence risk management in providing credit services.